Donor Collectors Route Optimisation using Genetic Algorithm Method - Gigih, Priyandoko; Arofah , Siti Nur; Sahar, Nan Mad; Istiadi, Istiadi (International Journal of Electrical, Energy and Power System Engineering, 2020)
Searching for a route to take donation in terms of time and the shortest route is a must for the management because it can save time and effort. In order to make donations more efficient, a system is needed to provide recommendations for taking donation routes, one of which is using a Genetic Algorithm (GA) method. The GA can be applied in optimizing schedules, routes, and spaces. The results show that after testing two different routes with different maximum generation values of 50, 100, 500 and 1000, a maximum generation value of 50 can give optimal results.